Collagen supplementation - does it bring real benefits? - Kaziród, Karolina; Hunek, Adrian; Zapała, Magdalena; Wiśniewska-Skomra, Joanna; Chmielarz, Karolina; Tylutka, Kinga; Hapon, Anna (Quality in Sport, 2023)
Collagen is a protein and one of the main building blocks of our skin. It is found in bones, tendons, ligaments, internal organs, blood vessels, and the lining of the intestines. In our body, collagen enables the cohesion of tissues and organs, affects hydration, resistance and elasticity of the skin, reduces the risk of developing degenerative joint diseases. Its production decreases with age. As a result, more and more people are taking collagen supplements. It has been proven that doing so can bring many benefits to the body. Taking collagen orally can be an effective way to improve the quality of the skin, increase hydration and delay the aging process. Collagen peptides are potential therapeutic agents for treating osteoarthritis and maintaining joint health. Collagen supplementation may be an element of preventive medicine in the field of cardiovascular diseases. as it significantly reduces fat mass and increases lean mass, it also leads to lower LDL concentrations. A beneficial effect was also noted on hair and nails, as well as on brain function.